2015
DOI: 10.1093/ije/dyv094
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity as a cause of cardiovascular disease: a Mendelian randomization study

Abstract: Using MR methods, we provide support for the hypothesis that adiposity causes CHD, heart failure and, previously not demonstrated, ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
87
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 29 publications
16
87
0
Order By: Relevance
“…Consistent with previous studies [11][12][13][14] All results are β coefficients (SE) from the MR instrumental variable estimates using IVW and so reflect differences in mean outcome per one unit difference of the exposures for continuously measured outcomes and difference in log odds for binary outcomes (CHD/type 2 diabetes) *p < 0.05, **p < 0.01, ***p < 0.001 FI, fasting insulin; FPG, fasting plasma glucose; HDL-C, HDL-cholesterol; LDL-C, LDL-cholesterol; T2DM, type 2 diabetes mellitus; TG, triacylglycerols our understanding of which CHD risk factors mediate BMI effects. Our findings provide strong support for undertaking RCTs in obese people to test the effect of triacylglycerol reduction and glycaemic control on CHD risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies [11][12][13][14] All results are β coefficients (SE) from the MR instrumental variable estimates using IVW and so reflect differences in mean outcome per one unit difference of the exposures for continuously measured outcomes and difference in log odds for binary outcomes (CHD/type 2 diabetes) *p < 0.05, **p < 0.01, ***p < 0.001 FI, fasting insulin; FPG, fasting plasma glucose; HDL-C, HDL-cholesterol; LDL-C, LDL-cholesterol; T2DM, type 2 diabetes mellitus; TG, triacylglycerols our understanding of which CHD risk factors mediate BMI effects. Our findings provide strong support for undertaking RCTs in obese people to test the effect of triacylglycerol reduction and glycaemic control on CHD risk.…”
Section: Discussionsupporting
confidence: 93%
“…1) [11][12][13][14]. These studies used one-sample MR and were unable to undertake sensitivity analyses that have been developed for testing likely bias by pleiotropy [15].…”
Section: Introductionmentioning
confidence: 99%
“…In total, the genetic variants from the 3 identified loci explained 0.9% variation of plasma PAI‐1 levels in the Framingham Heart Study 28. This strength of IV is in the range of others that have been employed in successful MR studies, suggesting these variants could serve as a potential IV in MR analyses with risk factor, subclinical, and clinical outcomes 26, 29, 30…”
Section: Introductionmentioning
confidence: 86%
“…37 However, another MR study including 20,055 participants and 1,500 ischemic stroke cases found a statistically significant association of genetically predicted higher BMI, assessed with a genetic instrument comprising 32 BMI-associated SNPs, with increased risk of ischemic stroke (hazard ratio 1.83, 95% CI 1.05-3.20 per 4.5-kg/m 2 increase in BMI). 38 Chief strengths of this study include the large number of total ischemic stroke cases and data on etiologic subtypes of ischemic stroke. Moreover, as a result of the MR design, reverse causation bias was prevented and potential confounding was reduced because genetic variants are not associated with self-selected dietary and lifestyle factors that may affect results from observational studies.…”
mentioning
confidence: 99%